Optimization Analysis of Mechanical Properties of Fly Ash-Based Multicontent Gasification Slag Paste Filling Material - Denghong Chen; Tianwei Cao; Ran Chen; Chao Li (Advances in Civil Engineering)
In view of the difficult utilization of a large amount of coal-based solid waste produced by coal electrification in the Ningdong mining area, especially the large storage and low utilization rate of gasified slag, combined with the advantages of high paste filling concentration, fast efficiency, and low construction cost, it is of great significance to study the appropriate proportion of fly ash-based multicontent gasified slag paste filling material for green mining and large-amount utilization of gasified slag. Based on the microstructure, composition, and particle size distribution of gasification slag, fly ash, broken coal gangue, furnace bottom slag, and desulfurization gypsum tested by XRD, SEM, and particle size sorting screen, the mass fraction (X1), gasification slag content (X2), m (c): m (FA) (X3). 29 groups of schemes are designed by four factors : mass fraction X1 refers to the proportion of solid in the filling paste, the amount of gasification slag in the solid X2 refers to the proportion of gasification slag in the solid, and m (c): m (FA) X3 refers to the proportion of fly ash and cement in the solid excluding gasification slag, coal gangue, desulfurization gypsum, and furnace bottom slag. The amount of desulfurization gypsum in the solid X4 refers to the proportion of desulfurization gypsum in the solid. The flow and strength characteristics of each group are analyzed. It is found that before proportioning, coal gangue of 2.5∼5 mm accounts for 80.8%, furnace bottom slag of less than 2.5 mm accounts for 56.5%, fly ash of 20∼80% μm accounts for 80%, and fly ash of 10∼20% μm accounts for 90%. XRD patterns reveal that the main components of four solid wastes and cement are SiO2 and Ca3SiO5, and the chemical composition of desulfurization gypsum is Ca(SO4)(H2O)2. The regularity of size change tends to be consistent, and the uniaxial compressive strength of 3 days later in group thirteenth exceeds 0.991 MPa. Combined with the flow characteristics, it is determined that there are 6 optimization groups in the inclined ladder area with the expansion of 200∼250 mm and the uniaxial compressive strength of 0.6∼1.4 MPa. The compressive strength increases with the increase of the mass fraction of single-factor analysis. The response surface method of C shows that the significance of X1, X2, X3, and X4 decreases in turn. The central combination design is used to predict that the mix proportion of X1 is 84%, X2 is 15%, X3 is 1 : 5, and X4 is 7%, the content of coal gangue is 10%, and the content of furnace bottom slag is 5% which is the best. The supplementary experimental results show that σ3d is 1.35 MPa and the expansion is 200 mm. Combined with SEM, it is found that the microstructure before and after optimization is rich in hydration products and the internal structure is well cemented, which further explains σC. The above research provides important basic parameters for large-scale disposal and green filling mining which is difficult to deal with a large amount of stockpiled gasification slag.